1975
DOI: 10.1136/jnnp.38.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Babinski response: stimulus and effector.

Abstract: SYNOPSIS This is an electromyographic study of the activity in flexor and extensor muscles of the big toe in 22 patients with a Babinski sign and 49 controls, after mechanical or electrical stimulation of the sole. The results indicate: (1) the Babinski sign is mediated by the extensor hallucis longus (EHL), and not by the extensor hallucis brevis; (2) electrical stimuli may fail to activate the EHL in these patients, and conversely may evoke EHL reflexes in control subjects; (3) in skin reflexes, electrical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This was the case even though a damaged pyramidal tract was assumed to exist in the SCI subjects according to clinical and electrophysiological data. Therefore, it is concluded that the presence of a BS in SCI subjects does not primarily depend on the damage of a specific spinal level or on the pathways projecting onto the interneuronal zone of the lumbosacral cord [18] or of direct cortico-spinal projections [8,13]. Furthermore, it must be assumed that a minimal muscle tone is required to allow for the presence of a BS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This was the case even though a damaged pyramidal tract was assumed to exist in the SCI subjects according to clinical and electrophysiological data. Therefore, it is concluded that the presence of a BS in SCI subjects does not primarily depend on the damage of a specific spinal level or on the pathways projecting onto the interneuronal zone of the lumbosacral cord [18] or of direct cortico-spinal projections [8,13]. Furthermore, it must be assumed that a minimal muscle tone is required to allow for the presence of a BS.…”
Section: Discussionmentioning
confidence: 98%
“…The BS is thought to be part of the general withdrawal reflex synergy released by a lesion of supraspinal pathways that project onto the interneuronal zone of the lumbosacral cord [18]. At the same time, its presence also requires a lesion or functional deficit of those fibres projecting directly onto the motoneurons of the effector muscles [8,13]. The effector organ of the reflex is the extensor hallucis longus (EHL) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upgoing toe is not an oracle, but part of a disinhibited flexion reflex (Walshe, 1914), and indicates abnormal recruitment of the extensor hallucis longus-a physiological flexor muscleinto synergy with the tibialis anterior (Landau and Clare, 1959; van Gijn, 1975). Even slight activity in the extensor hallucis longus causes movement of the great toe, because the load is small compared with that of other flexor muscles of the leg.…”
mentioning
confidence: 99%
“…Stimulation was mechanical, according to the usual clinical method: slow stroking of the lateral plantar border and the transverse arch with a semi-sharp object (Dohrmann and Nowack, 1973). Reflexes evoked by short electrical stimuli do not discriminate between patients with a Babinski response and normal subjects (van Gijn, 1975); there is also some overlap when pin pricks are applied to the sole by a vibrator (Nakanishi et al, 1974). Another important advantage of the familiar mechanical stimulus is that it allows feedback towards the clinical situation: muscle fibre potentials reflect the discharge pattern of motoneurones more exactly than a quick succession of movements, at least theoretically, and the time sequence of these discharges can be studied on film.…”
mentioning
confidence: 99%